Peripheral tetra-cationic Pt(II) porphyrins photo-inactivating rapidly growing mycobacteria: First application in mycobacteriology. (November 2020) - Rossi, Grazielle Guidolin; Guterres, Kevim Bordignon; da Silveira, Carolina Hahn; Moreira, Kelly Schneider; Burgo, Thiago Augusto Lima; Iglesias, Bernardo Almeida; de Campos, Marli Matiko Anraku
Abstract: In this manuscript, we report, for the first time, the photoinactivation evaluation of tetra-cationic porphyrins with peripheral Pt (II)-bpy complexes in the photodynamic inactivation (PDI) of rapidly growing mycobacterial strains (RGM). Two different isomeric Pt (II)-porphyrins were synthetized and applied. PDI experiments in the strains of Mycobacteroides abscessus subsp. Abscessus (ATCC 19977), Mycolicibacterium fortuitum (ATCC 6841), Mycobacteroides abscessus subsp. Massiliense (ATCC 48898), and Mycolicibacterium smegmatis (ATCC 700084) conducted with adequate concentration (without aggregation) of photosensitizers (PS) under white-light illumination for 90 min showed that the most effective PS significantly reduced the concentration of viable mycobacteria. The present results show that positively charged porphyrins at the meta position (3-PtTPyP ) are more efficient PS against M. abscessus, M. fortuitum, M. massiliense, and M. smegmatis . The effectiveness of the molecule as PS for PDI studies is also clear with mycobacteria, which is strongly related with the porphyrin peripheral charge and coordination platinum (II) compounds and consequently their solubility in physiological media. Tetra-cationic PS may be promising anti-mycobacterial PDI agents with potential applications in medical clinical cases and bioremediation. Graphical abstract: Image 1 Highlights: Application of tetra-cationic Pt (II)-porphyrins against mycobacteria. Use of porphyrins in the treatment of mycobacteriosis. 3-PtTPyP tetra-cationic porphyrin meta isomer is very effectiveness in photo-inactivation of mycobacteria.